Comparative Study of Free Radical Grafting and Alkaline Conjugation for Enhanced Resveratrol Incorporation and Whey Protein Functionalities - Tanaporn Manochai; Suthaphat Kamthai; Thanyaporn Siriwoharn (Foods)
Incorporating health-promoting resveratrol into food products is challenging, primarily due to its poor solubility. Covalent conjugation is a promising, low-energy, and environmentally friendly strategy to overcome this limitation. This study compared the effectiveness of free radical grafting and alkaline methods for covalently conjugating whey protein isolate (WPI) with resveratrol. Conjugates were evaluated for molecular weight, structural characteristics, functional properties, and antioxidant activities. Both methods yielded conjugates with enhanced solubility relative to native resveratrol, with fold increases from 7.6 to 21.7 for the free radical grafting and from 8.1 to 23.6 for the alkaline method. Conjugates prepared via free radical grafting exhibited greater increases in molecular weight (10–100 kDa range), higher resveratrol incorporation (up to 17.6%), and superior functional properties compared to the alkaline conjugates (p < 0.05). Specifically, emulsifying activity, foaming capacity, and foaming stability improved by up to 64.7%, 45.8%, and 220.9%, respectively, compared to WPI. The antioxidant activities of the free radical grafting conjugates were 1.3- to 3.6-fold higher than those of alkaline conjugates. These findings highlight free radical grafting of WPI as a promising approach for incorporating resveratrol and improving the functionality of protein-based ingredients in functional food products.